Technology enhancement in village chicken farming and feed milling for Kooperasi Keluarga Wan Jalong - Wan Bakar, Wan Mohd Marzuki; Kasim, Azhar; Abdul Rahman, Nordin; Sabuddin, Amir Taufiq; Tajuddin, Zaidi; Harun, Rostam (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Kooperasi Keluarga Wan Jalong is a family-based cooperative with active involvement in crops and village chicken farming. Village chicken farming was started with own capital and initiative.This poultry operation has 4 separate entities, a breeder farm with potential breeder capacity up to 3,000 breeders, a grow-out farm with capacity exceeding 10,000 birds, a hatchery and a medium size feedmill. In August 2011, the Cooperative established its linkage with UPM where technical assistance was given in feed formulation. With the awarded KTP grant in June 2012, the scope of knowledge transfer was broadened to the above 4 entities. The first year of the program was focused on the enhancement of facilities. Workshop on the implementation strategy was held with the attendance of the Cooperative Board of Directors and the Academias. Up-to-date 1,000 village chicken breeders are already in the farm. They are managed accordingly adopting best farm practice. The formulation of feeds for the village chicken were improved, and the feedmill was put into operation using additional cheap ingredients to reduce the cost of feeding. With the current development, the Cooperative is benefiting by adopting efficient methods in running its activities.